Green Computing Awareness: A Case of a Philippine Public Higher Education Institution - Sabili, Mark Anthony P.; Ignacio, Aris E. (International Journal of Computing Sciences Research; Vol 5 (2021): Vol 5, 2020)
Purpose – The objective of the study is to identify the green computing awareness in the case of a Philippine public higher education institution. Method – The study adopted a descriptive research design that describes what exists in a situation and often accomplishes this by using descriptive statistics. It made use of a structured questionnaire and used quantitative data. Results – Generally, the employees have a commendable level of approval in line with knowledge, attitude, and behavior towards Green Computing practices. Conclusion – Employees have a very good understanding and acceptance in terms of Green Computing practices. Recommendations – The school management needs to provide their employees with Green Computing Awareness Trainings and Seminars to sustain their level of awareness about topics such as Green Computing trends and practices. Research Implications – School management should formulate policies that ensure the implementation of Green Computing practices in the overall organization.